A Kenmotsu metric as a conformal η-Einstein soliton - Roy, S.; Dey, S.; Bhattacharyya, A. (Carpathian Mathematical Publications, 2021)
The object of the present paper is to study some properties of Kenmotsu manifold whose metric is conformal η-Einstein soliton. We have studied certain properties of Kenmotsu manifold admitting conformal η-Einstein soliton. We have also constructed a 3-dimensional Kenmotsu manifold satisfying conformal η-Einstein soliton.